Gilgit-Baltistan Election and the Fate of the People: A Case Study of District Skardu – Challenges and Opportunities for Local Communities - Asif Abbas; Shoaib Malik; Muhammad Aamir Hussain; Mushahid Hussain; Muhammad Abbas; Muhammad Junaid; Saqlain Mehdi, (Dialogue Social Science Review (DSSR), 2025)
This research investigates the impact of electoral politics in Gilgit-Baltistan (GB), focusing on District Skardu as a representative case study. Despite high political participation, the local communities face systemic issues related to underdevelopment, weak governance, and inadequate representation. Using mixed methods including statistical analysis, surveys, and policy evaluation, this study explores the disconnect between electoral processes and community welfare. Key challenges such as lack of constitutional rights, poor infrastructure, and political marginalization are highlighted, along with emerging opportunities through local governance, youth involvement, and community-led initiatives. The study concludes with actionable recommendations for ensuring that elections become a tool for transformation rather than mere symbolic engagement.